ВИПРАВА ЯНА ОЛЬБРАХТА 1497 р. НА БУКОВИНУ ТА ЇЇ ВПЛИВ НА ВЗАЄМОВІДНОСИНИ МОЛДАВІЇ ТА ПОЛЬЩІ - Балух, Олексій Васильович; Балух, Олексій Васильович (Видавництво та друкарня Чернівецького національного університету, 2021)
The article analyzes military and political events in the Moldavian territory in the context of the history of Northern Bukovyna and versatile sides of the Polish-Moldavian relations related to the life in the Bukovynian land. The end of the 15th century proved to be quite tense for the Bukovyna, which became the scene of confrontation between the powerful states – Ottoman Empire, Hungary and Poland. In this period military-political situation in Moldavia was stabilized, but its relations with Poland were not settled. The Ottoman Empire’s subjugation of strategic ports belonging to Moldavia – Kiliya and Belgorod – prompted an immediate reaction of both Poland and Hungary. Both parties recognized the importance of the Moldavian buffer, visible in the fact that the guarantees of Moldaviakeeping its status appearedin almost all political agreements between Poland, Hungary and the Ottoman Empire in the second half of fifteenth centuries. The Polish-Turkish peaceful relations were disturbed in 1497 when the new Polish king Jan Olbracht decided to regain Kilia and Białogród. A well-prepared military and diplomatic Black Sea expedition turned into a war with Moldavia. Hospodar Stefan, initially favorable to the actions of the Kraków court, refused to allow the Polish army to march through Moldavian territory, fearing the sultan. The expedition was unsuccessful, and since the hospodar was the sultan’s vassal, it provoked a violent reaction from the Ottomans. The Polish King’s defeat determined Moldavia’s status as an entity under the formal political patronage of Hungary with strong influences from the Ottoman Empire. In the spring of 1498, ottoman army invaded the lands of the Crown and reached Jarosław. The second Turkish invasion took place in the fall of that year and reached the San River. As a result of the signing of the Polish-Hungarian-Moldavian peace treaty of 1499, the war between Poland and Moldavia was ended, conflicts were settled, and hospodar Stephen III received Poland and Hungary as allies.
Keywords: Northern Bukovyna; Moldavian State; military and political relations; Stephen III; Poland; Ottoman Empire; Hungary